Perlindungan Hukum Penyiaran kepada Anak terhadap Konten Pornografi dan Kekerasan menurut P3SPS pada Media Televisi - Hira Imandari; Qoniah Nur Wijayani (Lembaga Pengembangan Kinerja Dosen, 2024)
At this time, one of the electronic mass media that’s still loved by the majority people in the world is television, when other mass media such as radio and newspapers are starting to be abandoned and losing their popularity amidst the crazy impact of globalization and modernization, television is still showing it’s existence, through the variety shows by various national broadcasting institutions. In this case, children and teenagers occupy the top rank as the largest number of television viewers in Indonesia. Children and teenagers are a group of people who have a fairly fast learning ability, they can easily follow and learn what they see, hear and through what they experience, so in this case it can be concluded that television is an electronic audio visuals media make a significant contribution to children's learning and growth. But, what if the majority of television shows are not child-friendly, such as the many scenes of pornography, sexuality, physical and mental violence that are still freely shown, not in accordance with the age rating and standard broadcast hours set by the KPI? This research uses a qualitative research method with an approach using a literature review method, which means this research is guided by research journals and several books that have similar discussions, to find out the role of broadcasting law in protecting children against violent and pornographic content on television.